PEMANFAATAN MEDIA FLASHCARD PADA PEMBELAJARAN KOSA KATA BAHASA ARAB SISWA KELAS 2 SDI MUTIARA SUNNAH - Ikmala Dina Syarifa (ELEMENTARY: Jurnal Inovasi Pendidikan Dasar, 2026)
ABSTRACT Vocabulary (mufradat) mastery constitutes a fundamental component of Arabic language learning at the elementary school level. Nevertheless, students frequently encounter difficulties in retaining vocabulary and sustaining active engagement throughout the learning process. Existing studies have predominantly focused on the development of flashcard media or on measuring its effectiveness, while limited attention has been devoted to examining how the media is implemented within authentic classroom settings. This study aimed to describe the utilization of flashcard media in Arabic vocabulary instruction for second-grade students at SDI Mutiara Sunnah. A descriptive qualitative approach was employed, involving one Arabic language teacher and second-grade students as the research participants. Data were collected through classroom observations and documentation, then analyzed using an interactive process consisting of data reduction, data display, and conclusion drawing and verification. The credibility of the findings was ensured through technique triangulation. The findings reveal that flashcard media were systematically integrated into the opening, core, and closing stages of instruction, creating a continuous learning process through vocabulary introduction, repetition, and reinforcement. Visual representations enabled students to associate lexical forms with their meanings more effectively, enhanced their attention, participation, and learning enthusiasm, and assisted teachers in presenting learning materials in a more concrete manner that corresponded to the developmental characteristics of elementary school learners. These findings suggest that flashcard media function not merely as visual aids but as an instructional strategy that strengthens classroom interaction and promotes more meaningful learning experiences. The novelty of this study lies in its comprehensive qualitative description of the implementation process of flashcard media, students' responses, and the supporting as well as inhibiting factors influencing its use in Arabic language learning. ABSTRAK Penguasaan kosakata (mufradat) menjadi fondasi dalam pembelajaran bahasa Arab di sekolah dasar, namun proses pembelajarannya masih menghadapi tantangan karena siswa sering mengalami kesulitan mengingat kosakata dan belum terlibat secara optimal selama kegiatan belajar. Di sisi lain, kajian mengenai media flashcard lebih banyak diarahkan pada pengembangan produk maupun pengukuran efektivitasnya, sehingga dinamika penerapannya dalam pembelajaran yang berlangsung secara alami masih jarang dikaji secara mendalam. Penelitian ini bertujuan mendeskripsikan pemanfaatan media flashcard dalam pembelajaran kosakata bahasa Arab pada siswa kelas II SDI Mutiara Sunnah. Pendekatan kualitatif deskriptif digunakan dengan melibatkan seorang guru bahasa Arab dan siswa kelas II sebagai subjek penelitian. Data diperoleh melalui observasi dan dokumentasi, kemudian dianalisis secara interaktif melalui reduksi data, penyajian data, serta penarikan dan verifikasi kesimpulan, sedangkan kredibilitas temuan diperkuat melalui triangulasi teknik. Temuan penelitian memperlihatkan bahwa media flashcard terintegrasi pada setiap tahapan pembelajaran sehingga membangun kesinambungan aktivitas mengenalkan, mengulang, dan menguatkan penguasaan kosakata. Kehadiran representasi visual membantu siswa menghubungkan bentuk kata dengan maknanya, meningkatkan perhatian, partisipasi, dan antusiasme selama pembelajaran, sekaligus memudahkan guru menyajikan materi secara lebih konkret sesuai karakteristik perkembangan siswa sekolah dasar. Kajian ini menegaskan bahwa media flashcard tidak hanya berfungsi sebagai sarana visual, tetapi juga sebagai bagian dari strategi pembelajaran yang memperkuat interaksi belajar dan pengalaman belajar yang lebih bermakna. Kebaruan penelitian terletak pada penyajian deskripsi komprehensif mengenai proses implementasi media, respons siswa, serta faktor-faktor yang mendukung dan menghambat pemanfaatan flashcard dalam pembelajaran bahasa Arab.